Hubungan Korelasional Kualitas Tidur dengan Kejadian Anemia Pada Remaja Putri di SMP Negeri 1 Cabangbungin - Abdul Zaki; Mila Sartika; Previarsi Rahayu; Ananda Patuh Padaallah (Jurnal Ners, 2026)
Anemia remains a health problem among adolescent girls that can lead to decreased concentration, fatigue, and productivity. One factor that is thought to be related to anemia is sleep quality. This study aims to determine the relationship between sleep quality and anemia among adolescent girls at SMP Negeri 1 Cabangbungin in 2025. This study uses a quantitative design with a cross-sectional approach. The study sample consisted of 84 female students selected according to the research criteria. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while the incidence of anemia was determined based on hemoglobin level tests using an Hb meter with an anemia threshold of <12 g/dL. The results showed that 57.1% of respondents had poor sleep quality and 56.0% had anemia. Spearman's test showed a p-value of 0.000 (p < 0.05) and r = -0.685, indicating a strong relationship or correlation between sleep quality and the incidence of anemia in adolescent girls. There is a strong and significant relationship between sleep quality and the incidence of anemia among adolescent girls. Improving sleep quality is recommended as part of anemia prevention efforts in this population.Keywords: Adolescent girls, Anemia, Hemoglobin, Sleep quality.